Impact of phosphorus placement on corn rooting dynamics under long-term strip-tillage - Sindt, Marcie Renee (Kansas State University, 2017)
Soil profile phosphorus (P) distribution is known to influence rooting dynamics. However, it’s unknown if P placement in long-term no-till management influences root development in high P-testing soils. The research objective was to compare impacts of P placement on corn (Zea mays, L.) root development. Replicated field trials were conducted in Manhattan, KS on a long-term, strip-tilled, corn-soybean-wheat rotation. Five P treatments were applied to the corn rotation for 11 years and included a control (0 kg), 22 kg starter and 67 kg broadcast (BC+ST), 90 kg broadcast (BC), 22 kg starter and 67 kg deep band (DB+ST), and 90 kg deep band (DB) of P₂O₅ per hectare. This study was conducted in 2015 and 2016 – years 10 and 11 of the long-term study, respectively. All treatments tested above 20 ppm P, with highest concentrations at 10-15 cm for DB, and 0-5 cm for all other treatments. Root length treatment differences were observed primarily in the upper 35 cm during vegetative growth. In 2015, both total root length (TRL) and root length by depth were significantly less for starter P treatments. Though no TRL differences were observed in 2016, BC+ST exhibited reduced root length compared to BC across multiple depths. The BC and DB treatments had similar root growth in 2015. In 2016, greater TRL and root length across multiple depths were observed for BC compared to DB. Although grain yield was not affected, this study showed that P placement in high testing soils impacts root development, particularly during vegetative growth.
Keywords: soil; phosphorus; rootcorn